1994
DOI: 10.1177/001872089403600304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Speech Intelligibility Level on Concurrent Visual Task Performance

Abstract: Four experiments were performed to determine if changes in the level of speech intelligibility in an auditory task have an impact on performance in concurrent visual tasks. The auditory task used in each experiment was a memory search task in which subjects memorized a set of words and then decided whether authority presented probe items were members of the memorized set. The visual tasks used were an unstable tracking task, a spatial decision-making task, a mathematical reasoning task, and a probability monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Turatto et al 4 postulated that the auditory and visual response selection could not be shared across modalities, and attentional resources used for auditory responses detract from the central processing of the visual task. Payne et al 20 investigated the effect of a concurrent speech intelligibility task on several visual tasks and also concluded that higher-level cognitive sites are an important source of interference in auditory and visual dual tasks. They reported that interference among the auditory and visual tasks was "restricted to those visual tasks that tapped into the central processes of memory and decision-making (i.e., spatial processing, math processing)".…”
Section: Discussionmentioning
confidence: 99%
“…Turatto et al 4 postulated that the auditory and visual response selection could not be shared across modalities, and attentional resources used for auditory responses detract from the central processing of the visual task. Payne et al 20 investigated the effect of a concurrent speech intelligibility task on several visual tasks and also concluded that higher-level cognitive sites are an important source of interference in auditory and visual dual tasks. They reported that interference among the auditory and visual tasks was "restricted to those visual tasks that tapped into the central processes of memory and decision-making (i.e., spatial processing, math processing)".…”
Section: Discussionmentioning
confidence: 99%
“…One military study explored how speech intelligibility levels can affect visual task performance. 33 Researchers found that speech intelligibility impacted performance levels in a visual task that required use of short term memory and decision making, based on a sample of 28 subjects. However, intelligibility did not affect performance in a visual tracking task.…”
Section: Previous Researchmentioning
confidence: 99%
“…Pickett (1956) found that speech intelligibility remains relatively constant as speakers increase their vocal force from 50 to 78 dB, but diminishes above and below this range. Speech intelligibility has also been examined under less ideal conditions such as with degradation due to a chopping circuit that intermittently cuts out portions of the verbal message (Payne et al 1994), in the presence of noise (Broadbent 1958, Kryter, 1972, 1985, for synthetic speech (Robinson andEberts 1987, also see Simpson et al 1985 for a review of this literature) and under conditions of electronic versus natural ampli®cation (Tschopp and Beckenbauer 1991). Despite the abundance of literature on speech intelligibility under diverse conditions, the potential of intensity to alter processing requirements of speech stimuli has gained little attention.…”
Section: Introductionmentioning
confidence: 99%